The Emerging Social Neuroscience of Justice Motivation - Decety, Jean; Yoder, Keith J. (Trends in cognitive sciences, 2017)
Humans from a very early age are deeply sensitive to issues of justice and fairness, both in their own lives and in the lives of others. Most people are highly motivated to pursue justice and condemn injustice. Where does this concern for justice come from? Here we integrate findings in evolution, development, psychology, behavioral economics, and social neuroscience to highlight multiple potential drivers of justice motivation. We argue that justice motivation arises from complementary rapid heuristics and deliberation, each utilizing distinct and interacting neural circuitry. This framework is useful for explaining observed symmetries and asymmetries in responses to experiencing or observing injustice and may help to explain why individuals vary in their responses to injustice. From an early age, individuals are motivated by considerations of justice such as fairness and equity for both themselves and for others. However, people differ in their propensity to detect and react to injustice. Justice motivation involves fast, heuristic computations as well as controlled, deliberative ones. The processes underlying sensitivity to injustice for oneself and injustice for others are partially independent and sometimes exert opposing influences on behavior. Social neuroscience, by articulating multiple levels of organization across disciplines, is well suited to the identification of specific stages of information processing and circuits engaged in social cognition and decision-making that are susceptible to self-focused or other-focused justice sensitivity. Characterizing these influences contributes to a better understanding of how conflicting justice concerns influence decision-making and behaviors in human society.